Solidarity Through Localization? Humanitarian Responses to the COVID-19 Pandemic - Dany, Charlotte (Frontiers in Political Science, 2021)
This contribution discusses whether humanitarian aid is a suitable tool for expressing global solidarity in the COVID-19 pandemic. Based on the distinction between the concepts of humanitarianism and solidarity, as well as the example of the so-called “refugee crisis,” it provides a mixed answer: humanitarian aid and solidarity are, principally, different things, hardly comparable and, at times, even contradictory. However, the corona pandemic presents an opportunity for localization of humanitarian aid, which is an opportunity for greater solidarity with those most in need. To make humanitarian aid a real tool for expressing global solidarity, one would have to regard the recipients of aid as equals and strengthen their agency, as well as that of local and grassroots organizations in the most affected areas - much as the localization agenda demands.